Prenatal screening of down syndrome. - Rosli, Rozita (2006)

(untitled)
The present invention provides a method using polymerasa chain reaction (PCR) for detecting Down syndrom in the fetus of a pregnant woman by way of determining the increased concentration levels of supeoxide dismutase-1 (SOD-1) gene sequence in maternal extra-cellular body fluid. Accordingly, the present invention provides a method for screening Down syndrom fetus using DNA aplification promers and gene specific probe for specifically amplifying and quantifying superoxide dismutase-1 (SOD-1) gene in a pregnant woman. The invention also relates to a diagnostic kit for carrying out the invention method.